Система криптографического преобразования чисел линейными рекуррентными формами - Анисимов, А.В. (Кибернетика и вычислительная техника, 2016)
Рассматривается двухступенчатая система кодирования чисел, основанная на представлении чисел в виде aPn + bQn, где Pn и Qn линейные рекуррентные последовательности. Последовательности Pn и Qn определяются разложением в цепные дроби квадратичных иррациональностей вида (a + √b)/c. В системах симметричной криптографии числа a, b и c является ключами. Розглядається двоступенева система кодування чисел, заснована на представленні чисел у вигляді aPn + bQn, де Pn та Qn лінійні рекурентні послідовності. Послідовності Pn і Qn визначаються розкладанням в ланцюгові дроби квадратичних іррациональностей виду (a + √b)/c. У системах симетричної криптографії числа a, b і c є таємними ключами. The purpose of the article is to develop and study a nondeterministic system of cryptographic integer encoding by means of linear recurrent sequences. Methods. We used methods of continued fractions, properties of linear forms, and bijective encoding of natural numbers. Results. We proved as a theorem that such a system of encoding is absolutely resistant to passive crypto-attacks. With some further additions it is also resistant to stronger types of attacks.